2004
DOI: 10.1103/physrevb.69.024407
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo analysis of the tricritical behavior in a three-dimensional system with a multicomponent order parameter: The Ashkin-Teller model

Abstract: Our Monte Carlo ͑MC͒ method has been extended to determine the type of ordering, the character of phase transitions, and positions of the tricritical points in the three-dimensional Ashkin-Teller spin-lattice model on a cubic lattice, which is an example of a system with multicomponent order parameter. The precise and detailed analyses of the system's behavior at the ends of the lines of Ising-like phase transitions are performed and the corrected phase diagram in these regions is presented and discussed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…The latent heat values received here are consistent within the uncertainty intervals with the values obtained from the analysis of the behavior of the cumulants of the type of Challa V L [12] l 0.2197p14q at K 4 0.1 and l 0.3504p23q at K 4 0.17 as well as of Lee-Kosterlitz U L [11] l 0.223p15q at K 4 0.1, modified by us [7,10].…”
Section: The Results and Conclusionsupporting
confidence: 71%
See 1 more Smart Citation
“…The latent heat values received here are consistent within the uncertainty intervals with the values obtained from the analysis of the behavior of the cumulants of the type of Challa V L [12] l 0.2197p14q at K 4 0.1 and l 0.3504p23q at K 4 0.17 as well as of Lee-Kosterlitz U L [11] l 0.223p15q at K 4 0.1, modified by us [7,10].…”
Section: The Results and Conclusionsupporting
confidence: 71%
“…To confirm the applicability of this method, we compare results of our analysis with the ones obtained by us using the analysis of the behavior of the cumulants of the type of Challa V L [12] and Lee-Kosterlitz U L [11], modified by us [7,10]. The latter for the first time applied by us to the AT model what is explained in Section 2.…”
mentioning
confidence: 91%
“…[5] it was shown that the phase transitions on the line AHK′ are continuous, the universality class of the transitions on this line has never been determined and our preliminary results are the first real indication in this matter on the line HK′. The only exceptions are the regions close to the tricritical points A and K′, where the continuous phase transitions are of the Ising character [3]. The point A is the tricritical one for all three order parameters for which the line AH is the boundary of ordering.…”
Section: Introductionmentioning
confidence: 58%
“…[3] and the papers cited therein) is summarized in the caption of Fig. 1 where all phases are shown and explained, following the notation of Ditzian et al [4].…”
Section: Introductionmentioning
confidence: 98%
“…IATM has been investigated by mean field renormalization group technique [19,20], Monte Carlo Simulation (MC) [21,22,23,24,25,26,27], effective field theory (EFT) [28], transfer-matrix finite-size-scaling method [29], high and low temperature series expansion and MC [30], MC and renormalization group technique [31,32] and damage spreading simulation [33,34,35].…”
Section: Introductionmentioning
confidence: 99%